The labor market in Ireland, 2000-2016 - Adele Bergin; Elish Kelly (IZA World of Labor, 2018)
Ireland was hit particularly hard by the global financial crisis, with severe impacts on the labor market. The unemployment rate increased dramatically, and the labor force participation rate declined by four percentage points between 2007 and 2012. Outward migration re-emerged as a safety valve for the Irish economy, helping to moderate impacts on unemployment via a reduction in overall labor supply. As the crisis deepened, long-term unemployment escalated, creating significant policy challenges. Overall unemployment has been dropping rapidly since 2013, but remains above its pre-crisis level.
Keywords: J01; J08; J21; J60; J64; J68; 330; unemployment; migration; Ireland